MORPHODYNAMICS OF THE CHIRLEŞTI MUDFLOW (BUZĂU MOUNTAINS) - DAN BĂLTEANU; MIHAI MICU (Revue Roumaine de Géographie)
The paper undertakes a morphological and morphodynamic assessment of a 1,350 m-long mudflow, followed up in various phases since its occurrence that poses a great danger to one of the main Trans-Carpathian roads in Romania. The study relies on large-scalegeomorphological mapping and on aerial photos obtained over several time sequences (1977, 1992 and 2005),total station and DGPS surveys and laboratory analysis of some sliding plane rock variables. Assessments were aimed on highlighting the morphological, morphometrical and morphodynamic characteristics of the mudflowfunctional sectors. Mudflow reactivation episodes over the above-mentioned time interval alternated with periods of intense gully erosion and reactivations of upper sector slides.